Pre-COVID-19 evaluation of external debt, corruption and economic growth in South Africa - Ebenezer Gbenga Olamide; Andrew Maredza (Review of Economics and Political Science (REPS), 2023)
Purpose - This study is a pre-COVID-19 exposition of the existing situation about external debt-GDP relationship, incorporating corruption into the hypothesis, making South Africa the object of the study. The aim is to examine the causal relationship between corruption, economic growth and external debt, and in the end proffer solutions to the problems arising therefrom. Design/methodology/approach - The study employed ARDL technique on time series data running from 1990 to 2019 with real gross domestic product as the dependent variable and external debt, external debt servicing, corruption, inflation and capital formation as regressors. Necessary tests that include unit root, cointegration, CUSUM and CUSUMSq, normality, serial correlation and heteroscedasticity were performed on the model. Findings -The study shows that corruption, inflation and external debt servicing exert negative influences on economic growth while the effect of investment on growth was positive. External debt's effect in the short run was positive while its long-run effect on growth was negative. Among other things, the need to improve and strengthen public institutions in addition to targeting tax evaders and avoiders for increased government revenue were emphasized. Originality/value - The study incorporates corruption into the country specific debt-GDP debate as against earlier studies that excluded corruption in their time series analysis or that were cross-country based. The authors also exposit the existing knowledge of the debt-GDP hypothesis before the outbreak of COVID 19 pandemic. This is expected to serve as a precursor to subsequent studies on the rising debt of South Africa during and after the pandemic.
Keywords: 330; ARDL; Corruption; Economic growth; External debt; Debt-GDP; Pre-COVID-19